Beyond disclosure: Can firms be forced to spend their way to social responsibility? - Anantharaman, Divya; Manchiraju, Hariom; Misra, Shekhar (Review of Accounting Studies, 2026)
We study India’s regulation requiring firms to create board-level CSR committees and spend 2% of profits on CSR initiatives targeting environmental sustainability and local socioeconomic development. We examine whether such a mandate can meaningfully enhance corporate social responsibility. We find significant improvements in environmental and social ratings of Indian firms relative to matched global peers, particularly in community engagement and natural resource stewardship. Outcome-based measures, such as waste and resource use, also indicate real effects. Notably, improvements occur only in firms that substantially increase CSR spending and establish independent, expert committees; firms that merely comply superficially show muted effects. Our findings suggest that, despite criticisms of mandated CSR as paradoxical or potentially rent-seeking, such regulations can effectively promote socially responsible business practices when implemented with sufficient commitment and oversight.